Tensile strength and fracture behaviors of granite specimens after thermal treatment: Experimental and GBM numerical insights - Yan-Hua Huang; Hao Yin; Sheng-Qi Yang; Gan Feng; Ming-Xu Li; Kun-Bo Zhang; Wen-Ling Tian (Journal of Materials Research and Technology)
During geothermal exploitation of deep hot dry rocks (HDR), high-temperature reservoirs cool when exposed to water, potentially altering rock properties and fracture characteristics. To investigate the mechanical properties and fracture behaviors of granites under different cooling methods, granite samples were treated with natural cooling (NC) and water cooling (WC). Brazilian splitting tests were then performed to study the evolution of tensile strength with the change of temperature and cooling methods. 3D scans of fracture surfaces were employed to calculate roughness coefficients, correlating them with tensile strength. SEM observations revealed the thermal fracture mechanism, including thermal cracks, grain size, and water-induced weakening. A numerical model based on digital image processing (DIP) and the grain-based model (GBM) was developed, with coefficients of thermal expansion of different minerals incorporated. Simulated results closely matched the Brazilian test results. Tensile strength decreased significantly with temperature, with reductions of 25.6 %, 37.7 %, 70.7 %, and 73.8 % for NC conditions, while 30.6 %, 43.7 %, 81.1 %, and 84.2 % for WC conditions when the temperature rises from 200 °C to 800 °C compared to room temperature. The roughness of fracture surfaces increased with temperature, with maximum increases of 64.2 % and enhanced roughness at 800 °C. These findings offer insights into damage and fracture mechanisms in HDR reservoirs during geothermal exploitation.